Proteinograma sérico de veados-catingueiro (Mazama gouazoubira) criados em cativeiro obtido por eletroforese em gel de agarose e de poliacrilamida (SDS PAGE) Serum protein concentrations of captive brown brocket deer (Mazama gouazoubira) determined by means of agarosis and sodium dodecyl sulphate-polyacrylamide (SDS-PAGE) gel electrophoresis - A.M. Santana (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2008)
The serum protein concentrations of brown brocket deer (Mazama gouazoubira) obtained by agarosis gel and sodium dodecyl sulphate-polyacrylamide (SDS-PAGE) gel were determined from blood samples of ten adult healthy animals (six females and four males), monthly collected in the morning, during 12 months. The animals, maintained in individual stable and protected from noise, received ad libitum a diet of comercial ration and green roughage. Serum protein concentrations in agarosis gel revealed the presence of four protein fractions: albumin, alphaglobulin, betaglobulin, and gammaglobulin. Only serum concentrations of albumin were influenced by season, being values in spring higher than values in summer (4.15 x 3.64g/dl). Serum concentrations of albumin (4.05 x 3.75g/dl) were higher for female and alphaglobulin (0.39 x 0.53g/dl) werehigher for males. Results showed 34 proteins with molecular weights ranging from 18kD to 165kD. Significant differences between at least two seasons were found on values of 11 proteins. In conclusion, on account of the 10 animals been maintained in the same physical space and submitted to the same handling system, physiological variations, which are characteristic of this species, can be apointed as the reason of these differences.